Advertisement Remove all ads

Prove that (sinθ−cosθ)/(sinθ+cosθ)+(sinθ+cosθ)/(sinθ−cosθ)=2/(2sin^2θ−1) - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Prove that `\frac{\sin \theta -\cos \theta }{\sin \theta +\cos \theta }+\frac{\sin\theta +\cos \theta }{\sin \theta -\cos \theta }=\frac{2}{2\sin^{2}\theta -1}`

Advertisement Remove all ads

Solution

`LHS=\frac{\sin \theta -\cos \theta }{\sin \theta +\cos \theta}+\frac{\sin \theta +\cos \theta }{\sin \theta -\cos \theta }`

`=\frac{(\sin \theta -\cos \theta )^{2}+(\sin \theta +\cos \theta)^{2}}{(\sin \theta +\cos \theta )(\sin \theta -\cos \theta )}`

`=\frac{2(\sin ^{2}\theta +\cos ^{2}\theta )}{\sin ^{2}\theta-\cos ^{2}\theta `

`=\frac{2}{\sin ^{2}\theta -(1-\sin^{2}\theta )`

`=\frac{2}{(2\sin ^{2}\theta -1)}=RHS`

 

Concept: Trigonometric Identities
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×